2006
DOI: 10.1007/11908562_4
|View full text |Cite
|
Sign up to set email alerts
|

Software Process in Practice: A Grounded Theory of the Irish Software Industry

Abstract: Abstract. This paper presents the results of a Grounded Theory study of how software process and software process improvement (SPI) is applied in the practice of software development. This study described in this paper focused on what is actually happening in practice in the software industry. Using the indigenous Irish software product industry as a test-bed, we examine the approaches used to develop software by companies at various stages of growth. The study used the grounded theory methodology and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In some cases, it is seen as nearly essential for the business. These findings support prior studies [6,7,8] in VSEs in relation to adoption of lifecycle standards and indicate there is much work yet to be done.…”
Section: Discussionsupporting
confidence: 88%
“…In some cases, it is seen as nearly essential for the business. These findings support prior studies [6,7,8] in VSEs in relation to adoption of lifecycle standards and indicate there is much work yet to be done.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in the case of CMMI, an Australian study found that small organizations considered that adopting CMMI would be infeasible (Staples et al, 2007) and an Irish study found significant resistance due to negative perceptions surrounding levels of bureaucracy and required documentation (Coleman & O'Connor, 2006). Further investigation of the SEI CMMI by Staples and Niazi (2006) discovered, after systematically reviewing 600 papers, that there has been little published evidence about those organizations who have decided not to adopt CMMI.…”
Section: Problems With Standardsmentioning
confidence: 99%
“…Although commercial Software Process Improvement (SPI) models (such as Capability Maturity Model Integration for Development, CMMI-DEV) (SEI, 2010) have been highly publicized and marketed, they are not being widely adopted and their influence in the software industry therefore remains more at a theoretical than practical level (Coleman & O'Connor, 2006;O'Connor & Coleman, 2009). In the case of CMMI ® , evidence for this lack of adoption can be seen by examining the SEI (Software Engineering Institute) CMMI data for the threeyear period March 2008to March 2011(CMMI, 2011, which shows that worldwide during that period less than 3,500 individual appraisals were reported, which includes many divisions of the same company.…”
Section: Standards: Benefits and Drawbacksmentioning
confidence: 99%